Alpha and Kappa angle on postoperative visual quality in cataract surgery - Xiao-Na Chen; Ying-Yue Xiong; Jia Wei; Bin Luo; Ya-Li Gao (International Journal of Ophthalmology)
AIM: To explore the effect of Alpha angle and Kappa angle before multifocal intraocular lenses (MIOLs) implantation on postoperative visual quality of patients. METHODS: Before and 3mo after cataract surgery, Alpha angle and Kappa angle were collected using IOL Master 700, iTrace, and Pentacam for clinical observation. Postoperative visual quality indicators, including high-order aberrations (HOA), modulation transfer function (MTF) and point spread function (PSF), were collected using iTrace. multiple linear regression analysis was used to analyze the correlation of the Kappa angle and the Alpha angle with age, axial length (AL), anterior chamber depth (ACD), keratometry (K), lens thickness (LT) and corneal white to white distance (WTW). Pearson correlation coefficient was used to analyze the correlation between Alpha angle and Kappa angle; Bland Altman analysis was used to evaluate the consistency of pairwise detection results of three instruments. RESULTS: The Alpha angle was modeled as Alpha=2.230+0.003×age-0.036×AL-0.025×K-0.058×WTW and the Kappa angle was modeled as Kappa=0.685+ 0.003×age-0.013×K-0.061×WTW. The correlation between the total Alpha angle and Kappa angle of the three instruments was weakly positive (r=0.291, P=0.000). Comparing the measurement of Alpha angle and Kappa angle using three instruments, only IOL Master 700 and iTrace showed good consistency in measuring Kappa angle (P=0.4254). After 3mo of surgery, the Alpha angle and Kappa angle significantly decreased (P=0.011, 0.018; P=0.008, 0.036). △Kappa=1.136-0.021×AL-0.013×K. Kappa angle could positively predict HOA (β=0.18, P=0.000), MTF (β=0.171, P=0.000), PSF (β=0.088, P=0.000), Alpha angle cannot (P>0.05). CONCLUSION: The patients with older age, flatter K and shorter WTW should be alert to the possibility of larger Alpha angle and Kappa angle. Alpha angle should also consider the factor of AL. When selecting patients with MIOLs implantation, there is no need to consider the Alpha angle. Careful consideration should be given to the Kappa angle, and the preoperative standard of <0.5 mm can refer to △Kappa=1.136-0.021×AL-0.013×K and be appropriately relaxed.